2017
DOI: 10.1057/s41287-017-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

How Much Should We Trust Micro-data? A Comparison of the Socio-demographic Profile of Malawian Households Using Census, LSMS and DHS data

Abstract: This paper assesses the empirical representativeness of micro-data by comparing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…One caveat to this study is that it relies on self-reported income data, which is somewhat noisy. This is a recognized feature of data collected under large household surveys with comprehensive modules, such as the LSMS-ISA (Fraval et al, 2019; Tasciotti and Wagner, 2018; Wollburg et al, 2021). As described earlier, we addressed outliers through winsoring at the top and bottom 5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One caveat to this study is that it relies on self-reported income data, which is somewhat noisy. This is a recognized feature of data collected under large household surveys with comprehensive modules, such as the LSMS-ISA (Fraval et al, 2019; Tasciotti and Wagner, 2018; Wollburg et al, 2021). As described earlier, we addressed outliers through winsoring at the top and bottom 5%.…”
Section: Discussionmentioning
confidence: 99%
“…We recognise the uncertainties and inaccuracies associated with data collected from household surveys (Fraval et al, 2019; Tasciotti and Wagner, 2018; Wollburg et al, 2021). Nevertheless, the World Bank's LSMS is regarded as the de facto standard public database for analysis at the household level (https://www.worldbank.org/en/programs/lsms/initiatives/lsms-ISA#7).…”
Section: Methods and Datamentioning
confidence: 99%
“…The PDHS conducted four times in 1990-91, 2006-07, 2012 and 2017-18, have been deployed for our analysis. Particular importance -in the context of the four surveyshas been given to the collection of data on fertility levels [Tasciotti and Wagner (2018)]. The sample design adopted across waves is a stratified, clustered and systematic sample of households.…”
Section: Datamentioning
confidence: 99%
“…This increasing use and importance of data to inform policy decisions requires that the data underlying those decisions is of high quality. Data quality is thus the focus of much attention within the field of development economics (Jerven, ; Jerven & Johnston, ; Tasciotti & Wagner, ). Generally, however, there has been relatively little research examining the quality of data and the methods used to collect it.…”
Section: Introductionmentioning
confidence: 99%